Strengthening the Corn Processing Industry in Boyolali Regency Towards the Market Global Through E-Commerce - Rudianto, M; Noviani, Rita; Rahmawati, Rahmawati; Ubaidillah, Ubaidillah; Nurlaela, Siti (IMPOWERMENT SOCIETY, 2025)
Boyolali Regency is one of the largest corn producers in Central Java. The high productivity of corn encourages the Boyolali Regency government program to increase corn processing through coaching various SMEs and MSME corn processing and has been proposed as a pioneering regional superior product in the Strategic Plan of the Trade and Industry Service and the Cooperatives and Manpower Service of Boyolali Regency in 2025. One of the processed corn products is maning, increasing the marketing of Marning MSME as a superior product of Boyolali Regency with the triple helix method through collaboration between universities, business actors, and the Boyolali Regency government in order to realize quality UMKM, globally competitive, and sustainable. Global scale marketing is carried out to increase marketing expansion, implementing an approach to increase product visibility and sales with: e-commerce account development, online marketing strategies, packaging and branding, market and competition analysis, and training and education. Taking advantage of global market opportunities and e-commerce technology, as a marketing method for processed corn marning products offers great opportunities to increase sales and expand the market.